Cultural diplomacy : the case analysis of Lithuanian presidency of the Council of the European Union in 2013 - Dirmaite, Laura (2015)
A great range of various cultural events was presented in all member states of the European Union and overseas during the Presidency of the Council of the European Union in 2013. The greatest part of the cultural programme was implemented with the help of Lithuanian cultural attachés. The present Thesis focuses on cultural actors and projects involved in such particular term. Qualitative research through expert interviews (i.e. with Lithuanian cultural attachés in the United Kingdom, Sweden, Germany, Italy, Poland and the Permanent Representation of The Republic of Lithuania in the European Union in Belgium) was the research method used for this Master’s Thesis. The source material in this Master´s Thesis consists largely of recent books and articles about cultural diplomacy written by significant authors and scholars who greatly contributed to this issue. Also, some Lithuanian authors are presented in this paper when analysing the meaning of cultural diplomacy at Lithuanian level. In addition, some of the legal documents of the Republic of Lithuania must be interpreted when talking about the organizational structure of cultural diplomacy in Lithuania. Results indicate that a cultural attaché as individual institution abroad significantly contributes to various dynamic cultural processes. Lithuanian cultural attachés were strongly involved in processes of the Presidency regarding planning, organization and implementation in various level of the cultural programme. From the results of the thesis it can be concluded that cultural attachés are active, open and cooperating participants in cultural field that attract attention of Lithuanian organizations and artists as well as international cultural actors. Also, they are noticeable cultural disseminators outside Lithuanian borders. An attaché throughout cultural projects and activities introduces both international community and Lithuanian diaspora abroad with Lithuanian culture, arts and heritage.